2021
DOI: 10.12659/msm.932654
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound Imaging Features of Focal Splenic Tuberculosis

Abstract: Background The aim of this study was to characterize the contrast-enhanced ultrasound imaging features of focal splenic tuberculosis. Material/Methods We retrospectively analyzed the conventional ultrasound (US) and contrast-enhanced ultrasound (CEUS) imaging features of 22 patients with splenic TB confirmed by surgical histopathology or biopsy. Results Conventional US demonstrated that 15 of the 22 patients had a single lesion, while 7 had m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…CEUS has little value in improving the display rate of splenic tuberculosis, but it is superior to 2D US in evaluating the internal blood supply to the lesion ( 9 12 ). CEUS of splenic tuberculosis showed that the lesions were mostly non-enhanced ( Figure 4 ) ( 13 ). Thin septal enhancement was observed in some heterogeneous enhanced lesions ( Figure 5 ), and splenic lymphoma rare this sign, for splenic tuberculosis infectious disease, blood vessels are less damaging, remaining within the organization can exist in the spleen of lesions, and lymphoma rare necrosis, necrosis is more than spleen infarction, necrosis is more complete.…”
Section: Discussionmentioning
confidence: 99%
“…CEUS has little value in improving the display rate of splenic tuberculosis, but it is superior to 2D US in evaluating the internal blood supply to the lesion ( 9 12 ). CEUS of splenic tuberculosis showed that the lesions were mostly non-enhanced ( Figure 4 ) ( 13 ). Thin septal enhancement was observed in some heterogeneous enhanced lesions ( Figure 5 ), and splenic lymphoma rare this sign, for splenic tuberculosis infectious disease, blood vessels are less damaging, remaining within the organization can exist in the spleen of lesions, and lymphoma rare necrosis, necrosis is more than spleen infarction, necrosis is more complete.…”
Section: Discussionmentioning
confidence: 99%
“…If this is suspected, examination with a high-resolution linear transducer is recommended. Using CEUS, splenic lesions in the arterial phase showed a hyperenhancement, followed by either a slow washout or a persistent enhancement in the middle and late parenchymal phase [76]. A fast washout was the exception, but nevertheless was also possible.…”
Section: Spleenmentioning
confidence: 94%
“…These exceptional cases would therefore be difficult to differentiate from malignancies. There was also rim-like enhancement with central nonenhancement, like abscesses and septation-like enhancement [76]. Another study using CEUS in splenic manifestations of tuberculosis presented homogeneous enhancement (6.7%), heterogeneous enhancement (63.3%), and nonenhancement (30.0%).…”
Section: Spleenmentioning
confidence: 95%